Keragaan dan Produksi Jamur Tiram Putih (Pleurotus Ostreatus) Pada Media Serbuk Gergaji dan Ampas Tebu Bersuplemen Dedak dan Tepung Jagung - Sutarman Sutarman (Jurnal Penelitian Pertanian Terapan, 2012)
This study aims to determine the combined treatment between growth media and supplement that gives a white oyster mushroom growth responses as well as weight and harvest the best quality. Factorial experiment was repeated 4 times with the first factor of the type of media (bagasse and sawdust) and the second factor supplements (without supplements, rice bran, and corn flour). Combination treatment of bagasse and rice bran media gives the best response mushroom mycelium growing in terms of speed, the relative growth will be fruit, fruit caps the maximum size and weight of crop per baglog; while bagasse and corn flour to give the best response to fungi in the number and quality of the body fruit. Keywords: body fruit, bagasse, sawdust, rice bran, corn flour